Шляхи виживання представників творчих професій в містах України у 1917-1920 рр. - Попов, Вячеслав; Popov, Vyacheslav (My University, 2015)
У статті розглянуто повсякденне життя такої соціальної категорії міського населення, як люди творчих професій. Засобами їх пристосування до кризових умов були створення громадських об’єднань, продаж домашнього майна, гастрольні подорожі по містах і селах країни. У документах відсутні згадки про відмову будь-кого з представників творчої інтелігенції від звичного роду занять та про спробу опанувати іншу професію.The article examines the daily life of such social category of the urban population as creative professionals, which traditionally include scientists, writers, artists, musicians, painters. The specificity of their existence in a social and economic disaster was conditioned by the special nature of their activities and a certain reduction of its consumer attractiveness. Creative intelligentsia tried to unite in house committees, trade unions, co-operatives to ensure their needs. Within these organizations they implemented the allocation of scanty food and goods.
Ways of a Survival of Representatives of Creative Professions in the Cities of Ukraine in 1917-1920
Keywords: міське населення; творча інтелігенція; духовні потреби; National-democratic Revolution of 1917-1920 in Ukraine; urban population; creative intelligentsia; humanitarian spheres of culture; spiritual needs; entrepreneur